2003
DOI: 10.1017/s037346330300242x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Localization of Car-like Vehicles using Data Fusion of Redundant ABS Sensors

Abstract: A localization system using GPS, ABS sensors and a driving wheel encoder is described and tested through real experiments. A new odometric technique using the four ABS sensors is presented. Due to the redundancy of measurements, the precision is better than the method using differential odometry on the rear wheels only. The sampling is performed when necessary and when a GPS measurement is performed. This implies a noticeable reduction of the GPS latency, simplifying the data-fusion process and improving the q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…DMIs consist of wheel rotation sensors, such as differential odometers and ABS (anti-breaking systems) sensors (Bonnifait, Bouron, Meizel, & Crubille, 2003). Those are the one usually used in automotive localization systems.…”
Section: Differential Odometer Modelmentioning
confidence: 99%
“…DMIs consist of wheel rotation sensors, such as differential odometers and ABS (anti-breaking systems) sensors (Bonnifait, Bouron, Meizel, & Crubille, 2003). Those are the one usually used in automotive localization systems.…”
Section: Differential Odometer Modelmentioning
confidence: 99%
“…First, on-board vehicle sensors are applied to compensate for the INS error. Most of the previous researches are the integration of WSS with GNSS/INS to prevent INS error degradation during GNSS outages [5][6][7] Reference [8] developed five types of sensors integration algorithms for precise positioning, namely GPS/INS/WSS, GPS/INS/GS/YRS, GPS/INS/SAS, GPS/INS/WSS/SAS, and GPS/INS/WSS/GL/YRS/SAS. Second, on-board vehicle sensors are applied for dead reckoning (DR) to overcome the limitation of GNSS technique.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, as vehicle dynamic sensors can be applied to overcome the limitations of the GNSS technique, various studies combining GNSS and vehicle dynamic sensors have been conducted. Bonnifait et al [9] developed a localization system using GPS and WSS. They showed that a two-dimensional DR navigation based on WSS could estimate the horizontal positions with meter-level accuracy with GPS.…”
Section: Introductionmentioning
confidence: 99%